Diseño de un sistema de minigeneración eólica para el Centro de Interpretación del Parque Eólico Villonaco - Amaya Morocho, Juan Carlos (2024)
Using the abundant wind resources available in the Loja area, this work designs the Villonaco Wind Park Interpretation Center's wind mini-generation system. It was determined that the characteristics were the best components for adapting to the site's conditions for the design of the system. In order to determine wind flow behavior and the changes it undergoes when it interacts with the boundary layer, such as the building of the CIV (Villonaco Interpretation Center), RWIND software was employed, as well as a wind resource simulation based on CFD (Computational Fluid Dynamics). In the simulation, the average wind speed at the site location was determined. This along with other parameters collected from the technical literature were used for the design of the different components that make up the wind mini-generation system. The average design wind speed obtained by simulation was 8.6 m/s, and to obtain this speed it was necessary to introduce the reference speed with which RWIND generated a profile to be applied in the virtual wind tunnel; the reference speed was obtained through statistical analysis performed on the wind data obtained from the meteorological tower 1 of the Villonaco Wind Farm. An analysis of statistical data also revealed the critical wind speed, which is a crucial parameter in determining how the tower and fastening and anchoring systems should be designed, so that structural failures are not caused by the loads caused by the critical wind speed, ensuring that the entire system performs well. Keywords: Villonaco Wind Farm, , mini wind generation system, average design wind speed.